Evaluation of the implementation of SMK3 at the Grandmed Lubuk Pakam Hospital in 2024 - Sofia Diaz, Aya; Rambey, Harris; Tarigan, Layari (JURNAL KESMAS DAN GIZI (JKG), 2024)
SMK3 has been regulated in the guidelines for occupational safety and health in hospitals, but its implementation may face various challenges. Various factors such as the dynamics of the work environment, regulatory changes, and aspects of organizational culture can affect the effectiveness of SMK3 implementation. Permenkes No.66 of 2016 Article 4 states that SMK3 Hospitals include the determination of K3RS policies, K3RS planning, implementation of K3RS plans, monitoring and evaluation of K3RS, review and improvement of K3RS. This qualitative study aims to evaluate the implementation of SMK3 at Grandmed Lubuk Pakam Hospital. The informants were 5 people by conducting in-depth interviews equipped with a voice recorder. The research variables are K3RS policies, facilities and infrastructure, and human resources. The results of the study are that Grandmed Hospital has implemented the K3RS policy by having a commitment to implementing K3, but in its application to workers it has not been implemented properly, establishing a K3RS organization that plays a role in minimizing the risk of accidents and occupational diseases, providing complete K3 facilities and infrastructure in accordance with SOP, and only having one human resource expert as K3 personnel at the hospital. The suggestion given is that Grandmed Hospital Lubuk Pakam is expected to be able to improve professional human resources in the field of K3RS not only General K3, can build awareness of the importance of K3 through regular communication campaigns, plan monthly activity agendas such as role plays on the importance of K3 culture. Keywords: SMK3; K3RS Policy; Facilities and infrastructure; Human resources.